Usuwanie niewymierności z mianownika
a) mnożymy licznik i mianownik przez [tex]\sqrt{13}-2[/tex]
b) mnożymy licznik i mianownik przez [tex]\sqrt[3]{6^2}[/tex]
a)
[tex]\frac{12}{\sqrt{13}+2}=\frac{12}{\sqrt{13}+2}\cdot\frac{\sqrt{13}-2}{\sqrt{13}-2}=\frac{12(\sqrt{13}-2)}{(\sqrt{13})^2-2^2}=\frac{12(\sqrt{13}-2)}{13-4}=\frac{12(\sqrt{13}-2)}{9}=\frac{4(\sqrt{13}-2)}{3}[/tex]
b)
[tex]\frac{24}{\sqrt[3]{6}}=\frac{24}{\sqrt[3]{6}}\cdot\frac{\sqrt[3]{6^2}}{\sqrt[3]{6^2}}=\frac{24\sqrt[3]{6^2}}{\sqrt[3]{6^3}}=\frac{24\sqrt[3]{36}}{6}=4\sqrt[3]{36}[/tex]